A fundamental study of biomass oxy-fuel combustion and co-combustion - Farrow, Timipere Salome (2013)
While oxy-fuel combustion research is developing and large scale projects are proceeding, little information is available on oxy-biomass combustion and cocombustion with coal. To address this knowledge gap, this research conducted has involved comprehensive laboratory based fundamental investigation of biomass firing and co-firing under oxy-fuel conditions and compared it to conventional air firing conditions. First, TGA was employed to understand the fundamental behaviour of biomass devolatilisation, char combustion and nitrogen partitioning between volatiles and residual char. The results revealed that C02 did not have effect on the devolatilisation of sawdust at temperatures below 1100 grad. C due to higher mass transfer resistance of primary volatiles in C02 than in N2 at low temperatures. Secondly,. by optimising the devolatilisation procedure in a combustion system that simulates closely to an industrial scale such as drop tube furnace (DTF), the devolatilisation/char combustion characteristics of sawdust was investigated. The effect of CO2 on volatile yields, nitrogen partitioning and char burnout were all significant in relation to N2• While coal combustion additives are being used to enhance coal burnout, this study observed improved coal char burnout when biomass char was co-fired with coal char, again a faster burnout was observed in oxy-firing condition compared to air firing. This was due to the catalytic effect of biomass inherent alkali and alkaline earth metals. Similarly, improved volatile yields were observed during codevolatilisation. These fundamental results have provided insight into oxybiomass' firing and co-firing and the data can be used in appropriate CFD modelling to aid the design of oxy-biomass co-firing burners.